Brugada syndrome in Portugal: a cohort characterization. (3rd October 2022) - Oliveira, C; Silverio Antonio, P; Couto Pereira, S; Brito, J; Valente Silva, B; Alves Da Silva, P; Garcia, B; Martins, M; Raposo, M; Nunes Ferreira, A; Lima Silva, G; Carpinteiro, L; et al.
Abstract: Introduction: Brugada syndrome (BrS) is an inherited cardiac arrhythmic disorder that can lead to sudden death. Although SCN5A was the first pathogenic associated gene, other potential genes have been described. The relationship between SCN5A, spontaneous type 1 pattern and the predisposition to ventricular arrhythmias is not totally understood. Purpose: To characterize mutations in a Portuguese cohort with BrS and explore the genotype-phenotype association in terms of electrocardiographic pattern and arrhythmic risk. Methods: Prospective single-center study of patients (pts) with BrS. Genetic test included SCN5A direct sequencing from 2003 a broad panel of 120 genes associated with cardiomyopathies and arrhythmic disorders from 2018. Genetic test results were classified according to pathogenicity: mutations of unknown significance (MUS), mutations potentially pathogenic (MPP) and known pathogenic mutations (KPM). Kaplan-Meyer survival analysis was used to explore the association between genetic test results and the risk of arrhythmic events. Results: A total of 94 pts [46±12 years, 67% male, 64.9% with type 1 spontaneous pattern] were submitted to genetic testing. No relevant mutations were identified in 68pts and suspicious or pathogenic mutations were recognized in 26pts. The most frequent mutations occurred in SCN5A (N=20, 76.9%), and included 8 KPM: 4 in exon 23 (3 of them had the same mutation, c.4018G>A), 2 in exon 26 (c.4534C>T), 1 in exon 28 and 1 in exon 16. All MPP in SCN5A occurred either in exon 23 or 28. Considering MUS, different mutations were described in 6 different exons (8, 15, 18, 23, 25 and two in 28). Additionally, 6 pts presented MUS in other genes: SCN10A (N=2), ANK2 (N=2), SFM13A, CAV2 (associated with long QT), CACNA1D and PXDNL. We found no differences in the prevalence of spontaneous type 1 pattern considering gene mutation or mutation pathogenicity. A non-significant trend to higher arrhythmic risk was observed in pts presenting genetic mutations (either KPM, MPP or MUS), Long-Rank: 1.743, p=0.187. Conclusion: Gene mutations are identified in a minority of BrS pts, mostly at SCN5A gene. No association was noticed between genetic test results and the ECG pattern. However, pts with identified mutation presented a tendency to higher arrhythmic risk. At present time, genetic tests in BrS are only relevant for familial screening, but long-term collection of data is crucial to elucidate the genotype-phenotype relation and arrhythmic risk. Funding Acknowledgement: Type of funding sources: None.